Performance Analysis and Financial Projections of Shipping Companies - Riyanto, Didik; Ristiani, Sinta; Mulyani, Sri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The level of competition in the sea transportation industry continues to experience increasing growth every year. This research aims to determine the development of the financial performance of Shipping Company and what the future condition of the company's finances will be, as a business strategy to face competitive competition. This research uses a descriptive quantitative approach by measuring the 2019-2023 financial statements using Net profit margin, Return on Assets, Earning Before Interest Tax Depreciation and Amortization and compound annual growth, and projecting financial conditions for the next 5 years, namely 2024-2028 based on assumptions. Data collection techniques use secondary sources and primary sources, namely interviews and documentation. Results of historical financial research (Common Size, Trend and CAGR) in 2019-2023. The company experienced fluctuating conditions for financial performance (NPM, ROA, EBITDA) in 2019-2023. The company was quite good with a medium Z-Score level > 1.1 and projected conditions The Company's finances for 2024-2028 have increased significantly each year.